IMPLEMENTATION OF AFFIRMATIVE ACTION POLICY IN THE PROACTIVE RECRUITMENT PROGRAM FOR THE BORDER AREA IN THE IMPLEMENTATION OF THE SELECTION OF POLICE NON-COMMISSIONED OFFICERS AT THE RIAU ISLANDS REGIONAL POLICE IN 2020 - Ardi Kurniawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
One of the areas faced with the problem of HR recruitment for the National Police is the jurisdiction of the Riau Islands Police. Riau Islands Police has a border area that feels that it has not received justice because of its geographical location far from the regional committee (Panda) of Riau Islands. Long distances become an obstacle when regional sons participate in the recruitment and selection of candidates for police officers. The ni study aims to analyze the implementation of affirmative action policies in the border area proaktive recruitment program in the implementation of the selection of Police Non-Commissioned Officers at the Riau Islands Regional Police in 2020. Based on the results of the study, it is known that the principles and values of Affirmative Action have the potential and opportunity to bridge the socio-cultural problems that arise, while ensuring the representation and proportion of human resources in a deal in the population, geography, and culture characteristics of the community in the Polri organization. The principles and values of Affirmative Action have a significant impact on the quality of performance. The high workload and risk of working as a police officer must be balanced with strong driving factors and create a significant impact, especially in the aspect of member welfare. Even though in practice, the Riau Islands Regional Police is still faced with obstacles to the lack of interest in prospective registrants in the border area.